Supramolecular Nanodiscs Self‐Assembled from Non‐Ionic Heptamethine Cyanine for Imaging‐Guided Cancer Photothermal Therapy. Issue 2 (27th November 2019) - Mu, Xueluer; Lu, Yingxi; Wu, Fapu; Wei, Yuhan; Ma, Huihui; Zhao, Yingjie; Sun, Jing; Liu, Shaofeng; Zhou, Xianfeng; Li, Zhibo
Abstract: Supramolecular nanomedicines, which use supramolecular design to improve the precision and effectiveness of pharmaceutical practice and optimize pharmacokinetic profiles, have gathered momentum to battle cancer and other incurable diseases, for which traditional small‐molecular and macromolecular drugs are less effective. However, the lack of clinical approval of supramolecular assembly‐based medicine underscores the challenges facing this field. A 2D nanodisc‐based supramolecular structure is formed by a non‐ionic heptamethine cyanine (Cy7) dye, which generates fluorescence self‐quenching but unique photothermal and photoacoustic properties. These Cy7‐based supramolecular nanodiscs exhibit passive tumor‐targeting properties to not only visualize the tumor by near‐infrared fluorescence imaging and photoacoustic tomography but also induce photothermal tumor ablation under irradiation. Due to the nature of organic small molecule, they induce undetectable acute toxicity in mice and can be eliminated by the liver without extrahepatic metabolism. These findings suggest that the self‐assembling cyanine discs represent a new paradigm in drug delivery as single‐component supramolecular nanomedicines that are self‐delivering and self‐formulating, and provide a platform technology for synergistic clinical cancer imaging and therapy. Abstract : A two‐dimensional nanodisc‐based supramolecular structure is formed by using a nonionic heptamethine cyanine dye. The nanodiscs exhibit unique photothermal and photoacoustic properties to make imaging‐guided tumor therapy a reality. This strategy represents a new paradigm in drug delivery; single‐component supramolecular nanomedicines that are self‐delivering and self‐formulating, providing a technology platform for synergistic clinical cancer imaging and therapy.